Mengambil Upah Dalam Periwayatan Hadis Dan Implikasinya Terhadap Kualitas ‘Adalah Periwayat - Muhammad Zaki (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Taking Wages in the Transmission of Hadith and its Implications for the Quality of the Narrator's ‘AdalahThe practice of wage taking in hadith transmission becomes polemic among hadith scholars. For some scholars, wage taking for hadith transmission may undermine honor and implicates on the cancellation of ‘adalah status; therefore, its transmission is rejected. Interestingly, this article finds that some hadith transmitters received payment for the transmission; however,  the transmission is still accepted even by the famous imam of hadith. This article aims at revealing the attitude of hadith scholars toward some hadith transmitters taking wage when they transmit hadith and its implication on 'adalah quality. This article is library research whose main data sources are books of mushthalah al-hadits and al-jarh wa al-ta’dil. Data are analyzed using the descriptive-qualitative method and hadith critique (naqd al-hadith) approach. The result of this study is that there are some hadith transmitters taking wage in hadith transmission and they are assessed as 'adil by imam of hadiths scholar. Such practice can be accepted as motivation for taking wage in hadith transmission to fulfill the transmitters' daily needs as they are destitute. Such attitude, according to imam of hadith scholars, will not implicate the damage of muru’ah and the loss of 'adalah as long as the transmitters are consistent in their religious observance and they are not recognized as liars or perceived liars.